ANALISIS PERHITUNGAN DAN PELAPORAN PAJAK PENGHASILAN PASAL 22 ATAS PEMBELIAN PUPUK SUBSIDI TAHUN 2022 PADA PT PERUSAHAAN PERDAGANGAN INDONESIA CABANG YOGYAKARTA - Khasanah, Erlinda Nur; Sriniyati, Sriniyati; Susanti, Tia Ayu (MEASUREMENT : Jurnal Program Studi Akuntansi, 2024)
The aim of this research is to analyze the suitability of calculations and reporting of Income Tax 22 for the purchase of subsidized fertilizer in 2022 at PT Perusahaan Dagang Indonesia Yogyakarta Branch, based on Undang-Undang No. 36 of 2008 and Peraturan Menteri Keuangan No. 41/PMK.010/2022. This research was conducted using a descriptive research approach and quantitative secondary data sources. The results of the analysis showed that the calculation and reporting of Income Tax 22 for the purchase of subsidized fertilizer in 2022 at PT Perusahaan Dagang Indonesia Yogyakarta Branch has been carried out in accordance with Undang- Undang No.36 of 2008 and Peraturan Menteri Keuangan No. 41/PMK.010/2022. The rate used is 1.5% (one and a half percent) of the purchase price excluding VAT and is not final. Meanwhile, reporting by the treasurer/collector is carried out no later than 14 days after the tax period ends.